Hydration-mediated co-assembly enables whole-component utilization of flaxseed - Yanwen Sun; Xiangyang Liu; Xinyue Liu; Wanjun Han; Wei Yang; Yuanfa Liu (Food Hydrocolloids, 2026)

Study on the influence of different vehicle dynamic load frequencies on the dynamic characteristics and microstructure of remolded loess - Xu Duan; Zikang Yang; Qi Dong; Yu Zou; Zhaojiang Hu; Xun Qiu; Bo Wang; Wanjun Ye (Transportation Geotechnics, 2026)

Collision-free path planning for underwater gliders in time-varying currents via dual-archive niching differential evolution - Zezhong Li; Rongshun Juan; Yang Li; Shoufu Liu; Tianshu Wang; Shuaikun Shi; Leihao Du; Wanjun Feng; Zhongke Gao (Ocean Engineering, 2026)

ScCO2-driven multiscale porosity evolution in coal: Mineral-coupled reconstruction mechanisms and CO2-ECBM implications - Hengyi He; Peng Liu; Baisheng Nie; Xiao Cui; Jingtao Yang; Hao Zhang; Wanjun Chen; Song Bao (Fuel, 2026)

Multiscale Characterization of Anhydrous/Hydrous ScCO2 Effects on Coal: Time-Resolved Mineral-Pore Evolution and Divergent Control Mechanisms - Peng Liu; Wanjun Chen; Jingtao Yang; Baisheng Nie; Hengyi He; Hao Xu; Ang Liu (Gas Science and Engineering, 2026)

Ultrasonic enhancement of coalbed permeability: Frequency-dependent spatial differentiation remodeling of pore to fracture - Peng Liu; Wanjun Chen; Baisheng Nie; Hao Xu; Jingtao Yang; Zhengduo Zhao; Yulong Zhao; Liang Sun; Wei Liu (Fuel, 2026)

Oligo-cyanobacterial microalgae-bacteria granular sludge for mitigating cyanotoxin risk: Cultivation, characteristics, and formation mechanism - Bingdang Wu; Yu Zhai; Shiqi Li; Yuling Yang; Donglin Cao; Wanjun Wu; JingJing Yang; Tianyin Huang; Jinlong Zhuang (Journal of Environmental Management, 2026)

Study on shear strength prediction model of glass fiber-improved loess in seasonal frozen regions based on POA-XGBoost - Xiyue Wang; Wanjun Ye; Qianqian Ma; Hao Yang; Minghao Zhang (Cold Regions Science and Technology, 2026)

Time-varying tensile resistance mechanisms in slope-protecting alfalfa roots - Xu Duan; Zikang Yang; Bo Wang; Chuangchuang Chen; Jin Qu; Yuan Chang; Luyu Shi; Hanyang Yan; Qi Dong; Wanjun Ye (Plant and Soil, 2026)

Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.

Wave characteristics and wave energy resource assessment of the waters bordering China - Yanan Wu; Qingwei Zhou; Wanjun Jiang; Yang Bai; He Wu (Frontiers in Marine Science, 2026)
Wave energy is a clean and renewable marine resource with great development potential. The China Sea, including the Bohai Sea, Yellow Sea, East China Sea and South China Sea, has complex marine conditions. This study aims to clarify the wave characteristics and spatiotemporal distribution of wave energy resources in the China Sea, providing a scientific basis for its rational development and utilization. Using 30-year ERA5 wind field data (1995–2024) as input, the SWAN wave model was adopted to numerically simulate the wave field in the China Sea. The multi-year, seasonal, and monthly average wave and wave ennergy characteristics were analyzed, and wave energy resources was evaluated with wave energy rose diagrams at characteristic points. The Bohai Sea and Yellow Sea had low annual mean wave heights mostly below 1.2 m, the East China Sea 1.2–1.7 m, and high-latitude South China Sea up to 2 m. Most regions except the Bohai Sea and northern Yellow Sea had annual average energy flux densities exceeding 4 kW/m² , especially near Taiwan Island and South China Sea. Wave energy was richest in winter, followed by autumn, and poorest in spring; The characteristic points the dominant direction was east-northeast, with density mainly distributed in 1–10 s wave periods and 0–5 m significant wave heights. The China Sea has substantial wave energy potential. The spatiotemporal and directional characteristics identified provide important references for the design, planning and utilization of wave energy conversion projects in the region.

Dynamics of greenhouse gas emissions and methanogenic communities in sludge treatment wetlands: responses to intermittent loading - Junyu Liang; Yubo Cui; Kedong Ma; Xu Ma; Wanjun Zhang; Ruijie Tian; Yang Wang; Hongxuan Qi (Ecological Engineering, 2026)

Plasma exosomes reveal insights into bovine tuberculosis pathogenesis and diagnostic opportunities - Hangfan Zhou; Qilong Zhang; Songhao Jiang; Han Yang; Shujie Cui; Wenhui Wu; Lei Chang; Wanjun Zhang; Yuping Xie; Jiaqiang Zhu; Degang Zhou; Yao Zhang; et al. (Veterinary Microbiology, 2026)

Drinking water quality criteria value estimation for representative haloacetamide disinfection byproducts via a benchmark dose approach based on an association analysis between drinking water exposure and altered liver function in a community population in Wuxi from Jiangsu province - Shunan Wang; Jingying Zhu; Wanjun Zhang; Chao Yang; Lingling Xu; Limei Chen; Yao Li; Run Zhou; Xinliang Ding (Environmental Pollution, 2025)

Constructing an effective exposure index through mobile signal data in guangzhou: a refined resilience assessment of COVID-19-Driven shifts in urban green space usage - Jintang Chen; Luyao Yang; Shan Li; Bin Chen; Wanjun Lu; Fengdeng Wan; Qiumeng Li; Yongheng Feng (Urban Forestry & Urban Greening, 2025)

Key odorants driving aroma transformation during aging process in Liubao tea: A sensory and chemical perspective - Ying Yang; Ruijin Qiu; Qiushuang You; Wanjun Ma; Yuhui Zhang; Yan Zhao; Gaozhong Yang; Yue Zhang; Zhi Lin; Yin Zhu; Haipeng Lv (Food Chemistry, 2025)

The challenges and progress of CAR-T cell therapy in the treatment of solid tumors - Kai Cui; Wanjun He; Na Huang; Songshan Zhu; Dan Jiang; Weiqiang Yang; Yiwei Zeng; Muhammad Asad Farooq; Guangxian Xu (Molecular and Cellular Biochemistry, 2025)

Destabilization mechanism of whipped cream during freeze-thaw cycles - Qiuling Huangfu; Wanjun Han; Yuanfa Liu; Xiuhang Chai; Wei Yang (Journal of Food Engineering, 2025)

Potato–rice and garlic–rice rotation increases soil phosphorus availability through phosphate-solubiliing bacteria and root exudates in upland–paddy cropping systems - Qi Liu; Wei Zhou; Zhiping Yang; Tao Wang; Yong Fu; Xueping Yue; Haixiao Xia; Youfeng Tao; Fei Deng; Xiaolong Lei; Yong Chen; Wanjun Ren (Agriculture, Ecosystems & Environment, 2025)

Whether aristolochic acid directly drives hepatocarcinogenesis: comprehensive investigations from mutational signatures to animal models - Lu Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Yanchao Yang; Tong Chu; Dayuan Zheng; Dongfan Yang; Wenzhe Ma (Archives of Toxicology, 2025)

The toxicity, bioaccumulation, and potential food safety risks of pentachlorophenol in broiler chickens - Yongpeng Jin; Fude Zhang; Ying Liu; Wanjun Zhang; Yutong Tang; Wenjun Yang; Yiqiang Chen (Journal of Hazardous Materials, 2025)

Anti-osteoporotic effects of peptide PASTGAAK derived from black-boned silky fowl on ovariectomized mice - Yang Qiu; Jiaxin Guo; Jie Zhang; Chenxu Xue; Wanjun He; Jiajin Zhu (Food Bioscience, 2025)

Three novel umami peptides from porcine bone hydrolysate and the analysis of the interaction with the Venus flytrap domain of umami taste receptors T1R1/T1R3 - Jie Zhang; Yang Qiu; Jiaxin Guo; Wanjun He; Chenxu Xue; Zixin Wang; Jiajin Zhu (Food Bioscience, 2025)

Electrostatic self-assembly assisted construction of MXene/MoO3 hybrid aerogel for free-standing supercapacitor electrodes - Feitian Ran; Bowen Tan; Meijie Hu; Shulin Deng; Kai Wang; Wanjun Sun; Jifei Liu; Xiaobin Yang (Chemical Engineering Journal, 2025)

Creating a gene-indexed EMS mutation library of Zheng58 for improving maize genetics research - Leelyn Chong; Huihui Su; Yingpeng Liu; Lingling Zheng; Lianying Tao; Hai Bie; Di Xiao; Yang Yang; Wanjun Zhang; Jing Zhang; Jifei Ren; Huafeng Liu; et al. (Theoretical and Applied Genetics, 2025)

Dry season residual straw reduces nitrous oxide emissions during rice season in upland-paddy rotation systems by inhibiting soil denitrification - Tao Wang; Chengyang Ji; Wei Zhou; Hong Chen; Yong Chen; Qi Liu; Tao Cao; Zhiping Yang; Yong Fu; Xueping Yue; Fei Deng; Xiaolong Lei; et al. (Biology and Fertility of Soils, 2025)

Muti-Biomarker Approach and IBR Index to Evaluate the Oxidative Stress of Nanoplastic on the Clams, Meretrix meretrix and Sinonovacula constricta - Linlan Lv; Wanjun Feng; Ke Sun; Weihong Zhao; Fengjuan Jiang; Mohsen Mohamed; Lei Li; Yue Yang; Yingying Zhang; Yanming Sui; Xuexing Dong (Journal of Ocean University of China, 2025)

Species discrimination of Fritillaria Bulbus using PCR-CRISPR/Cas12a-based nucleic acid detection - Dongfan Yang; Yanchao Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Wenzhe Ma (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Toxicological risk assessment of triadimenol for human exposure, broiler health, and food safety - Yutong Tang; Ying Liu; Yongpeng Jin; Fude Zhang; Wanjun Zhang; Sunlin Luo; Jianjun Zang; Wenjun Yang; Yiqiang Chen (Food and Chemical Toxicology, 2024)

Effects of the pesticide carbendazim on broiler chicken health and carbendazim residue levels in broiler tissues - Wanjun Zhang; Yutong Tang; Ruiqi Fan; Fude Zhang; Yongchen Li; Jianjun Zang; Wenjun Yang; Zongyi Wang; Xiaoyan Yuan; Yuan Yang; Yiqiang Chen (Veterinary Research Communications, 2024)

Three-dimensional fluorescence combined with alternating trilinear decomposition and random forest algorithm for the rapid prediction of species, geographical origin and main components of Glycyrrhizae Radix et Rhizoma (Gancao) - Hengye Chen; Lixue Ren; Yinan Yang; Wanjun Long; Wei Lan; Jian Yang; Haiyan Fu (Food Chemistry, 2024)

Novel cow dung-doped sludge biochar as an efficient ozone catalyst: Synergy between graphitic structure and defects induces free radical pathways - Yuxuan Yang; Kedong Ma; Yubo Cui; Ke Zhao; Yuning Lu; Wanjun Zhang; Peijing Kuang; Xuejun Zou (Environmental Research, 2024)

Nano effect fluorescence visual sensor based on Au-AgNCs: A novel strategy to identify the origin and growth year of Lilium bulbs - Siyu Wang; Wanjun Long; Liuna Wei; Wenyu Cheng; Hengye Chen; Jian Yang; Haiyan Fu (Food Chemistry, 2024)

MsSPL12 is a positive regulator in alfalfa (Medicago sativa L.) salt tolerance - Shiwen Lin; Jie Yang; Yanrong Liu; Wanjun Zhang (Plant Cell Reports, 2024)

Low-temperature CO selective catalytic reduction denitrification and sulfuric acid regeneration mechanism of Cu-Ce/AC catalyst poisoned with zinc salt - Zhenjing Wen; Bangfu Huang; Zhe Shi; Wanjun Li; Liubin Luo; Gaoyong Zi; Linjing Yang (Fuel, 2024)

Smartphone-based electrochemical sensor for cost-effective, rapid and on site detection of chlorogenic acid in herbs using biomass-derived hierarchically porous carbon synthesized by a soft-hard dual template method - Wanjun Jiang; Zhonghui Zhuo; Xiaohua Zhang; Hai Luo; Lu He; Yuling Yang; Yangping Wen; Zhong Huang; Peng Wang (Food Chemistry, 2024)

Mutation of a highly conserved amino acid in RPM1 causes leaf yellowing and premature senescence in wheat - Wenjia Zhang; Zhaoheng Zhang; Qian Chen; Zihao Wang; Wanjun Song; Kai Yang; Mingming Xin; Zhaorong Hu; Jie Liu; Huiru Peng; Jinsheng Lai; Weilong Guo; et al. (Theoretical and Applied Genetics, 2023)

Preharvest glycerol treatment enhances postharvest storability of orange fruit by affecting cuticle metabolism - Zhifeng Zhu; Wanjun Mei; Ruixue Li; Huan Liu; Shuying Chen; Hongbin Yang; Rangwei Xu; Taojiang Huang; Jingsong Xiang; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2023)

The correlation between upper body grip strength and resting-state EEG network - Xiabing Zhang; Bin Lu; Chunli Chen; Lei Yang; Wanjun Chen; Dezhong Yao; Jingming Hou; Jing Qiu; Fali Li; Peng Xu (Medical & Biological Engineering & Computing, 2023)

Distribution, source investigation, and risk assessment of topsoil heavy metals in areas with intensive anthropogenic activities using the positive matrix factorization (PMF) model coupled with self-organizing map (SOM) - Wanjun Jiang; Lishan Meng; Futian Liu; Yizhi Sheng; Sheming Chen; Jilong Yang; Hairu Mao; Jing Zhang; Zhuo Zhang; Hang Ning (Environmental Geochemistry and Health, 2023)

Endogenous salicylic acid mediates melatonin-induced chilling-and oxidative-stress tolerance in harvested kiwifruit - Wanjun Guo; Chuyao Zhang; Ruiqin Yang; Siyi Zhao; Xinru Han; Zhiying Wang; Sufang Li; Hui Gao (Postharvest Biology and Technology, 2023)

Solar radiation utilization of five upland–paddy cropping systems in low-light regions promoted by diffuse radiation of paddy season - Qi Liu; Zhiping Yang; Wei Zhou; Tao Wang; Yong Fu; Xueping Yue; Hong Chen; Youfeng Tao; Fei Deng; Xiaolong Lei; Wanjun Ren; Yong Chen (Agricultural and Forest Meteorology, 2023)

Carbon emission evaluation of prefabricated concrete composite plates during the building materialization stage - Xiaojuan Li; Wanjun Xie; Ting Yang; Chengxin Lin; C.Y. Jim (Building and Environment, 2023)

Target-allele-specific probe single-base extension (TASP-SBE): a novel MALDI–TOF–MS strategy for multi-variants analysis and its application in simultaneous detection of α-/β-thalassemia mutations - Qiong Chen; Xuexi Yang; Weilun Huang; Ziyan Li; Mingli Xu; Yang Li; Fangchao Tao; Zhengyi Huang; Xu Yang; Xuefeng Zhao; Linxiao Jiang; Wanjun Zhou (Human Genetics, 2023)

Enhanced adsorption of benzo(a)pyrene in soil by porous biochar: Adsorption kinetics, thermodynamics, and mechanisms - Wanjun Wang; Jiaxin Lin; Shaobin Shao; Haojia Chen; Jiawei Dai; Yan Yang (Journal of Environmental Chemical Engineering, 2023)

UHPLC-QTOF-MS-based untargeted metabolomics and mineral element analysis insight into the geographical differences of Chrysanthemum morifolium Ramat cv. “Hangbaiju” from different origins - Wanjun Long; Xiuyun Bai; Siyu Wang; Hengye Chen; Xiao-Li Yin; Hui-Wen Gu; Jian Yang; Haiyan Fu (Food Research International, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Short-term exposure to six air pollutants and cause-specific cardiovascular mortality of nine counties or districts in Anhui Province, China - Guoao Li; Huanhuan Zhao; Mingjun Hu; Jialiu He; Wanjun Yang; Hanshuang Zhang; Zhenyu Zhu; Jinliang Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Differences in Rice Productivity and Growth Attributes Under Different Paddy-Upland Cropping Systems - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Wanjun Ren (International Journal of Plant Production, 2022)

Effects of carbon dioxide and green space on sleep quality of the elderly in rural areas of Anhui Province, China - Guoao Li; Zhenyu Zhu; Mingjun Hu; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2022)

Six air pollutants and cause-specific mortality: a multi-area study in nine counties or districts of Anhui Province, China - Guoao Li; Huabing Wu; Qi Zhong; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Zhenyu Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Molecular characterization and phylogenetic analysis of Wx genes of four diploid species of the Triticeae genera Eremopyrum, Psathyrostachys, and Henrardia - Shoufen Dai; Junru Li; Jiangwei Huang; Zhi Zhai; Wanjun Yang; Qianyu Liu; Yuanyuan Zuo; Zhongping Song; Jian Li; Gang Liu; Guoyue Chen; Yuming Wei; et al. (Genetic Resources and Crop Evolution, 2021)

Residual nitrogen from preceding garlic crops is important for double-cropped rice - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Nkrumah Malik; Wanjun Ren (Nutrient Cycling in Agroecosystems, 2020)

Separation and preparation of N-glycans based on ammonia-catalyzed release method - Meifang Yang; Ming Wei; Chengjian Wang; Yu Lu; Wanjun Jin; Xi Gao; Cheng Li; Langhong Wang; Linjuan Huang; Zhongfu Wang (Glycoconjugate Journal, 2020)

GABAergic Abnormalities Associated with Sensorimotor Cortico-striatal Community Structural Deficits in ErbB4 Knockout Mice and First-Episode Treatment-Naïve Patients with Schizophrenia - Chengcheng Zhang; Peiyan Ni; Yikang Liu; Yang Tian; Jinxue Wei; Bo Xiang; Liansheng Zhao; Xiaojing Li; Xiaohong Ma; Wei Deng; Wanjun Guo; Rongjun Ni; et al. (Neuroscience Bulletin, 2020)

Interaction Between Variations in Dopamine D2 and Serotonin 2A Receptor is Associated with Short-Term Response to Antipsychotics in Schizophrenia - Liansheng Zhao; Huijuan Wang; Yamin Zhang; Jinxue Wei; Peiyan Ni; Hongyan Ren; Gang Li; Qiang Wang; Gavin P Reynolds; Weihua Yue; Wei Deng; Hao Yan; et al. (Neuroscience Bulletin, 2019)

Testing the role of genetic variation of the MC4R gene in Chinese population in antipsychotic-induced metabolic disturbance - Yamin Zhang; Hongyan Ren; Qiang Wang; Wei Deng; Weihua Yue; Hao Yan; Liwen Tan; Qi Chen; Guigang Yang; Tianlan Lu; Lifang Wang; Fuquan Zhang; et al. (Science China Life Sciences, 2019)

Carbon concentrations of components of trees in 10-year-old Populus davidiana stands within the Desertification Combating Program of Northern China - Huitao Shen; Wanjun Zhang; Jiansheng Cao; Xiang Zhang; Quanhong Xu; Xue Yang; Dengpan Xiao; Yanxia Zhao (Frontiers of Earth Science, 2016)

The dehydration-induced ERECTA gene, MsSIK1, from alfalfa improved water use efficiency in transgenic Arabidopsis - Peng Guo; Hongxu Wei; Wanjun Zhang; Baoling Yang; Yajing Bao (Acta Physiologiae Plantarum, 2016)

Carbon storage capacity of different plantation types under sandstorm source control program in Hebei Province, China - Huitao Shen; Wanjun Zhang; Xue Yang; Xiuping Liu; Jiansheng Cao; Xinhua Zeng; Xin Zhao; Xuexun Chen; Wenxi Zhang (Chinese Geographical Science, 2014)

Tracking miRNA precursor metabolic products and processing sites through completely analyzing high-throughput sequencing data - Li Guo; Hailing Li; Jiafeng Lu; Qi Yang; Qinyu Ge; Wanjun Gu; Yunfei Bai; Zuhong Lu (Molecular Biology Reports, 2012)